TAREKAT AND PEACE BUILDING: A STUDY OF THE INCLUSIVISM OF THE COMMUNITY OF TEREKAT SYATTARIYYAH IN THE NAGARI OF SUNGAI BULUAH PADANG PARIAMAN REGENCY - Sefriyono Sefriyono (Islam Futura, 2020)
The life of tareqah community which is rarely eksplored is their social activity like their inclusiveness towords other religious communities. This paper eksplores the inclusiveness of community of Tarekat Syattariyyah in the nagari of Sungai Buluah Padang Pariaman Regency. The inclusiveness of community of Tarekat Syattariyyah based on the ortodoxy of Ahlussunnah Wal Jamaah that they have, namely Shafi’i Fiqh, Ash’Ariyah Theology and Al-Gazali Sufism. This ortodoxy is also called the Wasathiyah Islamic Ortodoxy. This ortodoxy is used to reject the salafi preaching, because the salafi preachers claim the religious patterns of the nagari community as bid’ah and liberal. While their acceptance of Nias-Christian based on the inclusiveness of the values of Tarekat Syattariyyah, namely: first, basically, the diversity of religion is the will of God. Second, all of the descendants of Adam are glorified by the God. Third, all humans are created from the one Nur, it is the Nur of Muhammad. Based on the above doctrine, hate each other caused of  religion contraradict with the tareqah values.